2007
DOI: 10.1590/s1516-35982007000400014
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho, variáveis fisiológicas e comportamento de bezerros mantidos em diferentes instalações: época seca

Abstract: were raised from birth to 70 days of age in one of the following housing systems: (1 -hutches; 2 -shadecloth; or 3 -with no shelter. Calves raised with no shelter showed higher rectal temperatures and respiratory rates in the afternoon. It was also observed that calves spend most of the time outside the hutches. There were no differences among housing systems for behavior measurements as well as for body weight, average daily weight gain, starter intake, and feed efficiency. In all three housing systems calves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
2
1
0
1
Order By: Relevance
“…These results corroborate searches made by McKnight (1978) who analysed the performance of Holstein calves in temperate region and Cunha et al (2007), who studied the performance of crossbred Holstein × Zebu calves in tropical regions. Both authors found decreases in the occurrence of diarrhea in animals that consumed higher amounts of concentrate and therefore, less need for drug intervention compared to animals that consumed less amount of concentrate during milk feeding stage.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These results corroborate searches made by McKnight (1978) who analysed the performance of Holstein calves in temperate region and Cunha et al (2007), who studied the performance of crossbred Holstein × Zebu calves in tropical regions. Both authors found decreases in the occurrence of diarrhea in animals that consumed higher amounts of concentrate and therefore, less need for drug intervention compared to animals that consumed less amount of concentrate during milk feeding stage.…”
Section: Resultssupporting
confidence: 88%
“…-1 , thatched roof = 1.083 kg d -1 , P = 0.832) and no interaction between roof type and supplementary lighting on concentrate intake at 3rd (P = 0.880), 4th (P = 0.775), 5th (P = 0.772), 6th (P = 0.401), 7th (P = 0.390), 8th (P = 0.349), 9th (P = 0.456) and 10th week of age (P = 0.737). These results are in accordance with studies by Cunha et al (2007), who also found no significant effects on the average daily consumption of concentrate among calves during milk feeding stage housed in shelters covered with different materials compared with concentrate consumption of calves reared in the open field.…”
Section: Methodssupporting
confidence: 92%
“…Portanto, este é um sinal de que os animais intensificaram os processos latentes de perda de calor na tentativa de manter a temperatura corporal dentro da normalidade fisiológica (Cunha et al, 2007). Os valores da temperatura retal (TR) variaram de 38,8 a 39,0 °C (Tabela 2); portanto, permaneceram dentro do intervalo considerado normal para rebanhos leiteiros que, de acordo com Robertshaw (2006) podem variar de 38,0 a 39,3 ºC.…”
Section: Resultsunclassified
“…They suggested that measurement of the normal range of diurnal fluctuations could be a valuable indication of the ability of bovine calf support on thermal stress. Cunha et al (2007aCunha et al ( , 2007b, studying crossbred Holstein × Zebu calves, noted that the respiratory rate and rectal temperature of the animals showed higher average values in the afternoon. These results agree with the rectal temperature readings in the present study, because this time the environment was characterized by high temperatures (Table 1), where the animals received the greatest amount of heat.…”
Section: Resultsmentioning
confidence: 99%